Think India the rise of the world's next superpower and what it means for every American - Rai, Vinay (Dutton, 2007)
With 1.1 billion residents, the world's largest democracy is poised to dominate the world stage. One of India's wealthiest men gives an insider's view into his country's dynamic transformation, revealing the forces and unique characteristics behind India's meteoric rise. India is not just software, outsourcing, and faraway call centers. With the economy soaring at 8 percent a year, India is a medical and pharmaceutical frontrunner, an R&D powerhouse, a rising manufacturing hub, and an up-and-coming cultural trendsetter in areas from fashion to film. And the world is taking note: Western companies from Lockheed Martin to McDonald's are moving in and research centers for Fortune 500 companies are popping up everywhere. Meanwhile, the U.S. military is forging close ties. Steel tycoon turned educator Vinay Rai, who now runs one of India's two private universities, couples with geopolitical writer Melissa Rossi to map out the rising new India.--From publisher description.